2014
DOI: 10.1128/aem.02342-14
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of the Pseudomonas aeruginosa Quinolone Signal and Related Alkylhydroxyquinolines by Rhodococcus sp. Strain BG43

Abstract: A bacterial strain, which based on the sequences of its 16S rRNA, gyrB, catA, and qsdA genes, was identified as a Rhodococcus sp. closely related to Rhodococcus erythropolis, was isolated from soil by enrichment on the Pseudomonas quinolone signal [PQS; 2-heptyl-3-hydroxy-4(1H)-quinolone], a quorum sensing signal employed by the opportunistic pathogen Pseudomonas aeruginosa. The isolate, termed Rhodococcus sp. strain BG43, cometabolically degraded PQS and its biosynthetic precursor 2-heptyl-4(1H)-quinolone (HH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
25
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 55 publications
0
25
0
Order By: Relevance
“…Secretion of inhibitory secondary metabolites, among them AQs, is thought to grant fitness advantages during colonization of different habitats, infection of hosts or competition within polymicrobial communities (Long et al ., ; Harvey et al ., ). Not surprisingly, detoxification mechanisms against AQs have evolved during the arms race between the respective metabolite producers and coexisting organisms (Müller et al ., ; Birmes et al ., ; Thierbach et al ., ). In this study, we demonstrate AQs to be brominated at position 3 by the marine bacterium Microbulbifer sp.…”
Section: Discussionmentioning
confidence: 99%
“…Secretion of inhibitory secondary metabolites, among them AQs, is thought to grant fitness advantages during colonization of different habitats, infection of hosts or competition within polymicrobial communities (Long et al ., ; Harvey et al ., ). Not surprisingly, detoxification mechanisms against AQs have evolved during the arms race between the respective metabolite producers and coexisting organisms (Müller et al ., ; Birmes et al ., ; Thierbach et al ., ). In this study, we demonstrate AQs to be brominated at position 3 by the marine bacterium Microbulbifer sp.…”
Section: Discussionmentioning
confidence: 99%
“…Based on in vivo and in vitro biotransformation experiments, we previously proposed a pathway for AQ conversion by R. erythropolis BG43 involving HHQ hydroxylation to PQS by a monooxygenase, followed by cleavage of the heterocyclic ring and alkyl chain removal to form anthranilic acid (37). These reactions were tentatively assumed to proceed analogously to steps of the 2-methylquinoline degradation pathway of Arthrobacter sp.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, we isolated Rhodococcus erythropolis strain BG43, which is capable of degrading HHQ and PQS to anthranilic acid (37,38). In the present study, we identified two sets of PQS-inducible genes located on a plasmid of strain BG43, which code for the enzymes of the degradation pathway.…”
mentioning
confidence: 82%
See 1 more Smart Citation
“…Moreover, it is capable of detoxifying the respiratory inhibitor 2-heptyl-4-hydroxyquinoline-N-oxide (HQNO), which is also produced by P. aeruginosa, by N-oxide reduction and hydroxylation. Like other R. erythropolis strains, strain BG43 contains the qsdA gene coding for an AHL lactonase (Müller et al, 2014). (Angiuoli et al, 2008), resulting in the annotation of 6,158 coding sequences (CDSs).…”
mentioning
confidence: 99%